Triggers of Workplace Violence in Emergency Departments: A Qualitative Study - Ibrahim Ayasreh; Ferial Hayajneh; Rana Al Awamleh; Mohammed ALBashtawy; Abdullah Al-Khawaldeh (Nurse Media Journal of Nursing, 2022)
Background: Workplace violence has become an alarming phenomenon facing healthcare systems worldwide. Emergency nurses were the most victimized from workplace violence incidents. There is a crucial need for conducting qualitative research addressing the unique contextual factors associated with workplace violence against emergency nurses in Jordan.Purpose: This study aimed to explore circumstances that Jordanian emergency nurses, who were victims of workplace violence from clients and/or their relatives, perceive as provocative for workplace violence events.Methods: A qualitative phenomenological method was used. Purposive sampling was utilized to recruit participants (n=15), who were victims of workplace violence, and working in eight emergency departments distributed over all regions of Jordan. Semi-structured face-to-face interviews were conducted. All interviews were recorded and transcribed into Arabic. The Interpretive Phenomenological Analysis (IPA) was used to manually analyse the gathered data. Member checking, prolonged engagement with data, stepwise replication, and personal journaling were used to enhance the rigor of the study.Results: Findings of this study resulted in four superordinate themes that represents the main individual, social, and organisational factors contributing to workplace violence in Jordanian emergency departments. These themes include aggressors’ misconceptions and misbehaviours with four subordinate themes, inappropriate Jordanian social customs with two subordinate themes, organisational circumstances of emergency department with two subordinate themes, and escalator nurses with three subordinate themes.Conclusion: This study highlighted how specific social, cultural, legal, and administrative aspects of Jordanian society were inappropriately employed so as to lead to spread of the workplace violence. This study has provided insight into the need for change at personal level of emergency nurses, social level of Jordanian public, and organizational level of hospital administration and environment in order to mitigate workplace violence incidence in emergency departments.